PESTS AND DISEASES OF ARABIKA COFFEE (Coffea arabika) IN HKM SOLOK RADJO, AIE DINGIN, LEMBANG GUMANTI DISTRICT, SOLOK DISTRICT, WEST SUMATRA PROVINCE - Leonardo, Viccy; Milantara, Noril (Sylva Jurnal Ilmu-ilmu Kehutanan, 2023)
Coffee was a plantation commodity that has quite high economic value among other plantation crops and plays an important role as a source of foreign exchange for the country, however, the pests and diseases that attack coffee plantations in HKM Solok Radjo are not yet known. This research aims to analyze pests and diseases of Arabica coffee (Coffea arabica) in HKm Solok Radjo, Aie Winter, Lembah Gumanti District, Solok Regency, West Sumatra Province. This research uses interview methods and field observations. The data analysis method in this research is descriptive analysis. The results of the research showed that the pests and diseases that were found in the coffee plantations were Hypothenemus hampei (fruit borer), coffee such as leaf rust disease (Hemilleia vastatrix), coffee fruit rot disease (Colletotrichum sp), coffee leaf spot disease (Cercospora coffeicola), upas fungus disease (Upasia salmonicolor). Pests and diseases in this plant are a nuisance because they can cause the plant to be damaged and even die. In handling it, a number of special steps are needed to eliminate pests and diseases in plants, including using pesticides or rotating crops.